Optimalisasi daya output pada Photovoltaic Penggunakan sistem tracking dan Fuzzy Logic Controller - Misti Qurniatun; Sugeng Dwi Riyanto; Muhamad Yusuf (P3M Politeknik Negeri Cilacap, 2023)
Photovoltaic is one of the environmentally friendly power plants. One of the problems using photovoltaic is the low efficiency level. Therefore, a method is needed to optimize photovoltaic performance. The use of fuzzy logic control for dual axis tracking system is used in this study to optimize photovoltaic performance. The dual axis tracking system functions to keep the photovoltaic always perpendicular to the direction of the sun's arrival so that it has more optimal output power. The input of the tracking system comes from the LDR sensor which is installed on each side of the Photovoltaic. This sensor is combined with RTC to anticipate weather changes (cloudy). LDR and RTC sensor data as input for fuzzy logic controller. Based on the results of the research, the output power of the Photovoltaic tracking system is 9.363 Watts or 46.82% of the Photovoltaic specifications. Meanwhile, static photovoltaic with conventional installation has a power of 7.247 Watt or 36.23% of the specification. So that Photovoltaic with fuzzy logic control for dual axis tracking system is 29.20% more optimal.